'In from the Periphery'? Re-framing the Reach of the Nineteenth-Century French Literary-Scientific Imagination. (2nd October 2021) - Orr, Mary
ABSTRACT: By investigating what it calls the literary-scientific imagination, this article refocuses critical attention towards new nineteenth-century French scientific knowledge in texts outside the realist 'canon'. Chateaubriand's Atala (1801) reveals French natural scientific nomenclatures illuminating significant, non-Western, knowledge. Scientific discovery in 'provincial' France proves discipline- and genre-defining in Adrien Cranile's little-studied Solutré (1872). Sand's fantastical-dystopian Laura ou Voyage dans le Cristal (1864) demonstrates important re-educational review of imperial scientific progress. The shared peripheral visions, effets de l'irréel and critical-creative scientific possibility of these indicative texts demonstrate the richness of the (nineteenth-century) French literary-scientific imagination for onward study.